The Strategic Plan of University in Facing Challenges of Industrial Revolution 4.0 (Case Study at Universitas Negeri Surabaya) - Nurhasan Nurhasan; Made Pramono; Martadi Martadi; Erta Erta; Hapsari Shinta Citra Puspita Dewi (Kelola: Jurnal Manajemen Pendidikan, 2020)
Industrial Revolution 4.0, as one of the main paradigms of the modern economy, requires higher education to straighten up to face this trend. Surabaya State University (UNESA) emphasizes the development of human resources (HR) as the main target of internal development in order to deal with industry 4.0. The academic community is encouraged to be sensitive to technology, by increasing intellectual capacity through civilization, training, competition, and / or schools. The study aims to identify the readiness of UNESA in facing challenges of Industrial Revolution 4.0. The implication of this research is to enrich the education management research about linking strategy between higher education and industry demand. The result showed that UNESA had moderate readiness in facing the challenges of Industrial Revolution 4.0 by deepening of intellectual capacity in the IT field through improving campus facilities and infrastructure, and procuring new learning technologies. Networking development with private sector is also becomes useful strategy in linking HR with the IT world related to Industry 4.0. Such a strategic effort under the prevailing laws and regulations enable UNESA to advance in pioneering the development of industry 4.0 on campus, especially for creating qualified graduates.